A safe and sensitive enterovirus A71 infection model based on human SCARB2 knock-in mice. Issue 24 (23rd May 2016) - Zhou, Shuya; Liu, Qiang; Wu, Xing; Chen, Pan; Wu, Xi; Guo, Yanan; Liu, Susu; Liang, Zhenglun; Fan, Changfa; Wang, Youchun
Abstract: Enterovirus A71 infection has become a severe threat for global public health. Vaccines for controlling and preventing Enterovirus A71 epidemics are highly demanded, however, vaccine evaluation has been hindered by the lack of suitable Enterovirus A71 infection animal models. Here we established an hSCARB2 knockin mouse model for real-time monitoring of enterovirus A71 infection in vivo . This model was sensitive to the infection of both replication-competent virus rEV71(FY)-EGFP and single round pseudotype virus pEV71(FY)-Luc. The intensity of bioluminescence correlated well with viral loads in infected tissues ( R = 0.86, P < 0.01). Pathological changes recapitulated human infectious and clinical features of enterovirus A71, including both general characteristics of "hand foot and mouth" and the severe symptoms in the CNS. A formalin-inactivated enterovirus A71 vaccine can elicit antibodies in R26-hSCARB2 mice, which play effective roles in protecting knockin mice against enterovirus A71 infection as indicated by bioluminescence. Therefore, this work provides a safe, sensitive and visualizing model for exploring mechanisms of enterovirus A71 infection and examining human enterovirus A71 vaccines and antiviral therapies.